2014
DOI: 10.3390/ijms151121229
|View full text |Cite
|
Sign up to set email alerts
|

From Plasminogen to Plasmin: Role of Plasminogen Receptors in Human Cancer

Abstract: Cell surface-associated proteolysis mediated by plasmin (PLA) is an essential feature of wound healing, angiogenesis and cell invasion, processes that are dysregulated in cancer development, progression and systemic spread. The generation of PLA, initiated by the binding of its precursor plasminogen (PLG) to the cell surface, is regulated by an array of activators, inhibitors and receptors. In this review, we will highlight the importance of the best-characterized components of the PLG/PLA cascade in the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 147 publications
0
65
0
Order By: Relevance
“…High levels of ENO-1 in cancer cells correlate with cancer progression and a poor clinical outcome of the affected patients (12). Ectopic overexpression of ENO-1 promotes cell proliferation, migration, invasion, and colony formation, thereby contributing to metastasis formation (19,21,45). The ability of ENO-1 to regulate so many processes related to cancer cell biology results from its participation in glucose metabolism and therefore in energy production, as well as its capability to modulate expression of genes involved in cell growth and inflammation (45).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ENO-1 in cancer cells correlate with cancer progression and a poor clinical outcome of the affected patients (12). Ectopic overexpression of ENO-1 promotes cell proliferation, migration, invasion, and colony formation, thereby contributing to metastasis formation (19,21,45). The ability of ENO-1 to regulate so many processes related to cancer cell biology results from its participation in glucose metabolism and therefore in energy production, as well as its capability to modulate expression of genes involved in cell growth and inflammation (45).…”
Section: Discussionmentioning
confidence: 99%
“…has been measured earlier in the plasma/serum of cancer patients. [23,[25][26][27][28][29] It was shown that cathepsin D and B activities in the serum of cancer patients are directly proportional to tumor progression and significantly higher compared with the control group. Resection of the tumor leads to a diminution in their activities two weeks and six week after the procedure.…”
Section: Protease Activity In Blood Plasmamentioning
confidence: 99%
“…To date, the molecular mechanism of this paradox has not been explained (Didiasova et al 2014) and may be due the incomplete understanding of the complex plasminogen-plasmin system and its interactions with other factors in tumours (Kwaan et al 2013). There is considerable controversy in the literature with some studies demonstrating PAI-1 is required for tumour growth (McMahon & Kwaan 2015) and tumour adhesion (Palmieri et al 2002), whereas others have found it to inhibit tumour cell binding to the ECM (Czekay et al 2003).…”
Section: Role Of Pai-1 In Ovarian Cancermentioning
confidence: 99%
“…Plasmin primarily functions to degrade not only fibrin clots but also ECM molecules either directly or indirectly by activating MMPs (Didiasova et al 2014). Plasmin proteolysis contributes to both physiological processes such as tissue remodelling and pathological processes including cancer invasion and metastasis (Castellino & Ploplis 2005).…”
Section: Role Of Pai-1 In Ovarian Cancermentioning
confidence: 99%